Yield of crops and soil resistance to penetration of the Alfisol under different management - Lima, Claudia Liane Rodrigues de; Reinert, Dalvan Jose; Reichert, José Miguel; Suzuki, Luis Eduardo Akiyoshi Sanches (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to evaluate the relationship among soybean and bean plant parameters and soil resistance to penetration of an Alfisol under no-tillage and conventional systems. In an experiment deployed under no-tillage in 1989, different wheel tracks of a 10-Mg machine were applied and different soil management systems were used in completely randomized design. Emergence speed index, foliar area index, height and yield of soybean and bean crops and soil resistance to penetration were quantified. The influence of soil resistance to penetration in foliar area index, height and productivity of beans is of 46, 51 and 59% respectively, whereas 55% of the height variation in soybean is explained by soil resistance to penetration. The critical value of soil resistance to penetration indicated for bean and soybean growth and yield is of approximately 1.7 and 1.9 MPa respectively.